SOIL AS A FACTOR INFLUENCING THE MANGROVE FOREST COMMUNITIES IN TALIDENDANG BESAR, RIAU - CECEP KUSMANA (BIOTROPIA, 1991)
One  transect of 10 m x 900 m was  constructed perpendicular  to  the sea edge  to know  the pattern  ofmangrove forest communities from the sea edge through the inland area. Then, one sample plot of 50 m x 50 mwas established at each forest community to explore its vegetation structure and soil characteristics. The results show that in Talidendang Besar area, there are three mangrove forest communities stretchingfrom the sea edge to the inland, namely Bruguiera parviflora, B. sexangula and B. sexangula-Nypa fruticans.The soil factors such as pH.EC (electrical conductivity), % K, % Na, C-organic, N-total, NH4 (ammonia), andCEC  (cation exchange  capacity) were  regarded  important  in  influencing  the  pattern of  the mangrove  forestcommunities.